2012
DOI: 10.14310/horm.2002.1358
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-induced senescence in pituitary adenomas and carcinomas

Abstract: ObjEcTIvE: The model of 'oncogene-induced senescence' (OIS), resulting in cell-proliferation arrest, has recently been suggested as a possible explanation for the non-progression of pituitary tumours to malignancy. The aim of the study was to compare the expression of β-galactosidase as a molecular marker of OIS, and p21/p16 as additional markers involved in mediating OIS, in pituitary adenomas, carcinomas and normal pituitary tissue. DESIGN: We performed: a) semi-quantitative immunohistochemistry (β-galactosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
23
1
3
Order By: Relevance
“…In agreement, Chesnokova et al (2008) have described senescence taking place predominantly in GH-secreting tumors, and to a lesser extent in PRL-secreting tumors. In addition, Alexandraki et al (2012) showed that SA-b-gal is overexpressed only in nonfunctional pituitary adenomas and GH-secreting tumors, and that in the context of senescence, these adenomas behave differently compared with ACTH-and PRL-secreting adenomas. Finally, as the great majority of pituitary carcinomas are derived from these latter types of adenoma, we might speculate that the lack or bypass of senescence in lactotrophs may permit the occasional prolactinoma to develop into a carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement, Chesnokova et al (2008) have described senescence taking place predominantly in GH-secreting tumors, and to a lesser extent in PRL-secreting tumors. In addition, Alexandraki et al (2012) showed that SA-b-gal is overexpressed only in nonfunctional pituitary adenomas and GH-secreting tumors, and that in the context of senescence, these adenomas behave differently compared with ACTH-and PRL-secreting adenomas. Finally, as the great majority of pituitary carcinomas are derived from these latter types of adenoma, we might speculate that the lack or bypass of senescence in lactotrophs may permit the occasional prolactinoma to develop into a carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence may constitute a plausible explanation for the benign nature of pituitary adenomas through the existence of an intrinsic predisposition of pituitary cells to limit uncontrolled proliferation through this cellular program. Some recent studies on pituitary tumorigenesis in transgenic mice (Chesnokova et al 2007(Chesnokova et al , 2008 and SA-b-gal in human pituitary tumor (Chesnokova et al 2011, Alexandraki et al 2012 have suggested that cellular senescence could be a significant mediator of growth cessation in these tumors. However, it still remains uncertain whether this cellular response takes place in the absence of direct genetic manipulation or during the development of pituitary proliferative injuries, indicating a possible physiological role for cellular senescence in the modulation of pituitary cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…OIS has been implicated in the arrest of pituitary tumors as in several other types of benign tumors. It has been shown in human and murine melanocytic nevi (Michaloglou et al 2005, Goel et Alexandraki et al 2012, Sapochnik et al 2016), but not in malignant adenocarcinomas. Cell senescence has a functional relevance in vivo, as a physiological mechanism limiting tumorigenesis in many diseases.…”
Section: Pathophysiological Role Of Il-6 In the Pituitarymentioning
confidence: 96%
“…Senescent cells show altered cell morphology, including increased lysosomal breakage, causing the lysosomal enzyme β-galactosidase to enter into the cytoplasm [54]. In a recent study, it has been suggested that the senescence pathway, as assessed by β-galactosidase IHC, is more activated in GH-secreting and nonfunctioning pituitary adenomas (NFPAs) [55]. Moreover, a negative correlation was found between Ki67 LI and cytoplasmic staining for both p16 and p21.…”
Section: Evolving Biomarkers Of Pituitary Tumor Aggressivenessmentioning
confidence: 99%